Penilaian Kinerja Rumah Sakit Dengan Menggunakan Pendekatan Balanced Scorecard: Systematic Review - Riwu, Samuel Lay; Wibowo, Adik (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2021)
Performance measurement has always only been seen from a financial perspective by all companies, including hospitals. The Balanced Scorecard (BSC) concept approach is an alternative in measuring performance. In addition to considering financial factors but also considering non-financial factors with four perspectives, namely customers, learning, and growth, internal business and finance itself, which are expected to provide a comprehensive assessment to management. The aim is to examine the application of the BSC in hospitals in various countries and assess the feasibility of its application to hospitals in Indonesia. The Method in this study uses a systematic review method, namely by studying investigative articles related to Hospital BSC published in ProQuest, EBSCO, SpringerLink, ScienceDirect and Scopus. Then, outside of UI access, article searches are also done through Google Scholar and apart from getting articles in Indonesian through Garuda. research and technology. The results of this study found that the benefits of implementing BSC in hospitals include increasing focus in the management process, balancing financial and non-financial performance, helping align goals, fostering a positive work culture and increasing work motivation, and encouraging changes in the work environment according to hospital needs. . This study also found that the main challenge in implementing the BSC in hospitals is the required adoption and implementation process. For hospitals in Indonesia, the BSC should be adopted and implemented gradually on a wider scale. Conclusion: This indicates that it is hoped that health agencies, including hospitals, can apply the BSC concept.